A COMPARATIVE STUDY OF DIGITAL CRYPTOCURRENCY INVESTMENTS BASED ON CURRENCY LAWS AND GLOBAL ECONOMIC REGULATIONS: A CASE STUDY OF THE BIG FOUR ASEAN COUNTRIES - Rico Nur Ilham; Irada Sinta; Fuadi; Arliansyah; Muhammad Multazam; Reza Juanda (RADJA PUBLIKA, 2025)
The rapid advancement of financial technology has introduced cryptocurrency as a revolutionary innovation in the global digital economy. Despite its growing popularity as an investment instrument, the legal and economic frameworks governing cryptocurrency remain fragmented, particularly within the ASEAN region. This research aims to analyze the influence of currency law clarity and global economic regulation on cryptocurrency investment, with investor trust serving as a mediating variable, in the context of the Big Four ASEAN countriesIndonesia, Malaysia, Singapore, and Thailand. This study employs a normative juridical and descriptive quantitative approach. Data were collected through documentation, expert interviews, and focus group discussions (FGD) involving financial institutions such as OJK, Bank Indonesia, BEI, Phintraco Sekuritas, and the Directorate General of Taxes. Quantitative testing was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 to assess the relationships among variables. The findings indicate that both currency law clarity and global economic regulation have a significant and positive effect on cryptocurrency investment, while investor trust plays only a limited mediating role. The strongest relationship is observed in Singapore, where the Payment Services Act (2019) provides comprehensive regulatory certainty and attracts institutional investors. In contrast, Indonesia’s fragmented regulatory stance recognizing crypto as a tradable commodity but not a legal tender creates uncertainty that weakens investor confidence. The study proposes the formulation of a “Triangle Policy Framework” integrating legal, economic, and fiscal regulation, and introduces the LCTR (Legal Cryptocurrency and Tax Revenue) model to optimize digital asset governance and fiscal transparency. This integrated model is expected to strengthen investor protection, enhance legal certainty, and support sustainable digital economic growth in the ASEAN region.